Post-exposure prophylaxis (PEP) efficacy of rifampin, rifapentine, moxifloxacin, minocycline, and clarithromycin in a susceptible-subclinical model of leprosy - Shannon M. Lenz; Jaymes H. Collins; Nashone A. Ray; Deanna A. Hagge; Ramanuj Lahiri; Linda B. Adams; Susilene Maria Tonelli Nardi (Public Library of Science (PLoS), 2020)
Background Subclinical infection with Mycobacterium leprae is one potential source of leprosy transmission, and post-exposure prophylaxis (PEP) regimens have been proposed to control this source. Because PEP trials require considerable investment, we applied a sensitive variation of the kinetic mouse footpad (MFP) screening assay to aid in the choice of drugs and regimens for clinical trials. Methodology/Principal findings Athymic nude mice were inoculated in the footpad (FP) with 6 x 103 viable M. leprae and treated by gastric gavage with a single dose of Rifampin (SDR), Rifampin + Ofloxacin + Minocycline (SD-ROM), or Rifapentine + Minocycline + Moxifloxacin (SD-PMM) or with the proposed PEP++ regimen of three once-monthly doses of Rifampin + Moxifloxacin (RM), Rifampin + Clarithromycin (RC), Rifapentine + Moxifloxacin (PM), or Rifapentine + Clarithromycin (PC). At various times post-treatment, DNA was purified from the FP, and M. leprae were enumerated by RLEP quantitative PCR. A regression analysis was calculated to determine the expected RLEP value if 99.9% of the bacilli were killed after the administration of each regimen. SDR and SD-ROM induced little growth delay in this highly susceptible murine model of subclinical infection. In contrast, SD-PMM delayed measurable M. leprae growth above the inoculum by 8 months. The four multi-dose regimens delayed bacterial growth for >9months post-treatment cessation. Conclusions/Significance The delay in discernable M. leprae growth post-treatment was an excellent indicator of drug efficacy for both early (3-4 months) and late (8-9 months) drug efficacy. Our data indicates that multi-dose PEP may be required to control infection in highly susceptible individuals with subclinical leprosy to prevent disease and decrease transmission. Author summary While multi-drug therapy (MDT) has been successful in decreasing the worldwide prevalence of leprosy, the new case detection rate, or incidence, remains consistent. These circumstances indicate that leprosy transmission is still occurring. Subclinical asymptomatic leprosy infections are considered a leading cause of ongoing transmission. One means to control this source is an effective post-exposure prophylaxis (PEP) regimen that would prevent both subsequent progression to clinical leprosy for the individual and transmission of the disease to others. Therefore, in this study, we used a modified kinetic mouse footpad screening assay and sensitive molecular bacterial enumeration in a susceptible-subclinical mouse model to identify effective potential PEP drug regimens for leprosy. Using these methods, we showed that a single dose PEP regimen is not effective in a susceptible host, and multiple intermittent doses of combination therapies are required. This model could provide useful pre-clinical information for the development of PEP regimens for leprosy.